2010
DOI: 10.1038/ismej.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of internal waves on the spatial distribution of Planktothrix rubescens (cyanobacteria) in an alpine lake

Abstract: The vertical and horizontal distribution of the cyanobacterium, Planktothrix rubescens, was studied in a deep alpine lake (Lac du Bourget) in a 2-year monitoring program with 11 sampling points, and a 24-h survey at one sampling station. This species is known to proliferate in the metalimnic layer of numerous deep mesotrophic lakes in temperate areas, and also to produce hepatotoxins. When looking at the distribution of P. rubescens at the scale of the entire lake, we found large variations (up to 10 m) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 41 publications
7
66
0
Order By: Relevance
“…Our results are in line with other observations of the patchiness in P. rubescens horizontal distribution in pre-and alpine lakes (Cuypers et al 2010;Sotton et al 2011). Large patches (, 500 m long) of dense Planktothrix biomass recurrently formed in the metalimnion during our sampling, with apparent effects on the local physicochemistry.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our results are in line with other observations of the patchiness in P. rubescens horizontal distribution in pre-and alpine lakes (Cuypers et al 2010;Sotton et al 2011). Large patches (, 500 m long) of dense Planktothrix biomass recurrently formed in the metalimnion during our sampling, with apparent effects on the local physicochemistry.…”
Section: Discussionsupporting
confidence: 81%
“…Short-term variations in the vertical distribution of P. rubescens due to displacement by seiches have been scarcely documented (Thomas and Mä rki 1949;Thomas 1950;Cuypers et al 2010;Carraro et al 2012), and there is no information on the variations in light conditions that are experienced by P. rubescens in situ. Comprehensive calculations indicated that vertical shifts significantly affect the net photosynthetic production balance because this metalimnetic population is located close to its photosynthetic compensation point (Walsby et al 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Average surface concentrations of DIP and TP can considered to be very good (r>0.85, Fig.8). The measured DIP concentrations during summer tend to be somewhat higher than the simulations, which might be, to some extent, due to the river uxes that not by internal waves or upwelling events that occur frequently in Lake Bourget (Cuypers et al, 2011), given their low growth rates (Bright and Walsby, 2000) and limited losses imposed by zooplankton (Kurmayer and Jüttner, 1999). On the other hand, their growth at 10-20 m depth (Fig.…”
Section: Discussionmentioning
confidence: 76%